KOMUNIKASI INTERPERSONAL DAN MOTIVASI KERJA PRAJURIT DALAM MENUNJANG KELANCARAN TUGAS OPERASIONAL TNI ANGKATAN UDARA DI PANGKALAN TNI AU SJAMSUDIN NOOR BANJARMASIN - Muhamad Arman; M. Yunus Jarmie; Zain Noktah Aslie (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
The success rate of a communication can be seen from the level of achievement of the purpose of communicating, if the purpose of communicating is not achieved then the communication can be said gagal.Ada some of the problems faced by the Air Force, especially therein that may interfere with the performance of the performance, can degrade performance, and bad for the organization. Restrictions problem in this thesis the two groups in terms of the smoothness of the material operational duties in the Air Force Air Force Base Sjamsudin Noor Banjarmasin is work motivation and interpersonal communication. Qualitative descriptive research with phenomenological approach, to determine the cases studied, focused on the characteristics, performed on a target or location or subject, namely the means of communication interpersonal relationships with the motivation to work in the Air Force Air Force Base Sjamsudin Noor Banjarmasin. Patterns of communication of research results that are run by the Air Force command. When the communication flowing through the official designated by the official hierarchy of the organization or by the job function of the message according to a formal communication network. Message in a formal communication network usually flows from top to bottom, from bottom to top or from the same level or horizontally. in principle, the placement of employees in the Air Force Sjamsudin Noor has been based on